Base-free enantioselective SN2 alkylation of 2-oxindoles via bifunctional phase-transfer catalysis - Litvajova, Mili; Sorrentino, Emiliano; Twamley, Brendan; Connon, Stephen J. (Beilstein Journal of Organic Chemistry, 2021)
N-Protected oxindole derivatives of unprecedented malleability bearing ester moieties at C-3 have been shown to participate in enantioselective phase-transfer-catalysed alkylations promoted by ad-hoc designed quaternary ammonium salts derived from quinine bearing hydrogen-bond donating substituents. For the first time in such phase-transfer-catalysed enolate alkylations, the reactions were carried out under base-free conditions. It was found that urea-based catalysts outperformed squaramide derivatives, and that the installation of a chlorine atom adjacent to the catalyst’s quinoline moiety aided in avoiding selectivity-reducing complications related to the production of HBr in these processes. The influence of steric and electronic factors from both the perspective of the nucleophile and electrophile were investigated and levels of enantiocontrol up to 90% ee obtained. The synthetic utility of the methodology was demonstrated via the concise enantioselective synthesis of a potent CRTH2 receptor antagonist.
Keywords: alkylation; base-free; cinchona alkaloids; CRTH2 antagonist; hydrogen-bonding; oxindole; phase-transfer catalysis